A cross-layering based autonomic approach for QoS support in heterogeneous wireless networks. (15th October 2008) - Ali Yahiya, Tara; Sethom, Kaouthar; Pujolle, Guy; Beylot, Andre-Luc
Future network environments will be heterogeneous and mobile terminals will have the opportunity to dynamically select among many different access technologies. Therefore, it is important to provide service continuity in case of vertical handoffs when terminals change the access technology. Two important wireless access technologies are WLAN (wireless local access networks) and WMAN (wireless metropolitan access networks) networks. In this article, we address several challenges related to a seamless integration of those technologies. We highlight important aspects for designing WLAN/WMAN interworking architecture on the basis of IEEE 802.21 framework. Then, we address important quality of service (QoS) issues for such interworked systems like degree of QoS support provided by the technologies, QoS mapping and signalling for vertical handoff. We combine concepts of autonomic computing in the design of the framework in order to use intelligence to provide flexibility, accessibility and transparency to the mobile users.